100 Days of Happiness [large type] : A Novel. - Brizzi, Fausto (Thorndike Press, 2016)
What if you knew you had only 100 days left to live? For Lucio Battistini, it's a chance to spend the rest of his life the way he always should have -- by making every moment count. Wistful, touching, and often hilarious, 100 Days of Happiness reminds us what matters most.